2019
DOI: 10.1155/2019/3182946
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless Tobacco and Its Adverse Effects on Hematological Parameters: A Cross-Sectional Study

Abstract: Background. Smokeless tobacco (SLT) as a drug substance has been used throughout the world although it has dangerous effects on human health. Among the 28 known carcinogens in SLT, tobacco-specific nitrosamines are considered to be the most potent. This has challenged the metabolic condition leading to a rise in the inflammatory status, increased apoptosis, and red blood cell (RBC) membrane damage. Therefore, the present study was undertaken to evaluate the adverse effects of SLT on hematological parameters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…Another important finding from hematological analysis of this study includes a positive relationship between SLT and increased WBC count. Shukla et al 14 in their study also reported that the count of leucocytes were higher in SLT users as compared to non-SLT users with the p value of 0.04, which is comparable with the findings of our study. A study performed by Alamgir et al 15 in Karachi indicated that gene-environment contact is a significant factor, as the chewable types of tobacco are held in the oral pouch for a long time, resulting in increased exposure of the mucosa to carcinogens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another important finding from hematological analysis of this study includes a positive relationship between SLT and increased WBC count. Shukla et al 14 in their study also reported that the count of leucocytes were higher in SLT users as compared to non-SLT users with the p value of 0.04, which is comparable with the findings of our study. A study performed by Alamgir et al 15 in Karachi indicated that gene-environment contact is a significant factor, as the chewable types of tobacco are held in the oral pouch for a long time, resulting in increased exposure of the mucosa to carcinogens.…”
Section: Discussionsupporting
confidence: 92%
“…SLT ingredients disrupt individuals’ cellular metabolism that contributes to shape changes and scale which have enormous consequences in terms of health maintenance. 14 In the present study, consumption of SLT has shown an adverse effect on CRP and changes in hematological parameters revealed association with SLT and had systemic adverse effects on the blood profile.…”
Section: Discussionmentioning
confidence: 47%
“…It suggested that tobacco chewers had vitamin de iciency due to nicotine-induced oxidative stress. Whereas another study reported a signi icant decrease in the level of MCV in tobacco users (Dass et al, 2013;Shukla et al, 2019). In the present study, MCH and MCHC level did not show a signi icant change in tobacco chewers as compared to controls.…”
Section: Resultscontrasting
confidence: 72%
“…In the present study, MCH and MCHC level did not show a signi icant change in tobacco chewers as compared to controls. However, some previous studies reported that the MCH level was found to be signi icantly increased in their studies (Dass et al, 2013;Biswas et al, 2015;Shukla et al, 2019).…”
Section: Resultsmentioning
confidence: 83%
“…Nicotine as an element present in all tobacco products might alter the suprarenal glands to produce more catecholamine [29], which may in uence leukocytosis causing damage and in ammation to tissues [30].…”
Section: Discussionmentioning
confidence: 99%